Studies on carbohydrate xenoantigens - Christiansen, D.; Mouhtouris, E.; Ramsland, Paul; Sandrin, M. (2012)
Naturally occurring and elicited anti-carbohydrate antibodies play a major role in immune responses to xenografts. The original obstacles associated with the Gal antigen have been largely resolved by the generation of knockout pigs. In contrast, much less is known about the nature and role of non-Gal carbohydrate antigens and the antibodies recognizing these. These antibodies can be identified and characterized by enzyme-linked immunosorbent assay. Furthermore, the biological significance of the non-Gal antigen(s) can be determined by expression of the relevant glycosyltransferase(s) by transfection and analyzed by antibody and/or lectin binding. © 2012 Springer Science+Business Media, LLC.